EKONOMI POLITIK “BERITA WARGA” DI RADIO PRFM BANDUNG (Studi Kasus tentang Jurnalisme Warga di Radio PRFM Bandung) - Slamet Parsono; Farid Soleh Nurdin; Pin Arya Pinandita (Lembaga Penelitian Universitas Langlangbuana, 2020)
Radio PRFM is one of the radio media that uses citizen information as radio news material. Information citizens are considered effective in collecting, managing, and disseminating the information to audiences. The activities of citizens in conveying this information constitute one of the activities of citizen journalism. This study aims to examine citizen information that became news of citizens in Radio PRFM in the political economy communications perspective Vincent Mosco. This study describes how the news of citizens experiencing commodification of content, commodification of workers and commodification audiences. Similarly, news of citizens experiencing the process of spasiaslisasi to reach the audience by overcoming the barriers of space and time. Economic Theory This communication politics also examines the structure, where PRFM becomes a medium against citizen journalists as (agents) and form audiences (structure). This study uses the Robert K. Yin case study method to generate a description of the findings in a certain time. The findings obtained by this research, radio news using citizen journalism network including low cost but can get big advantage that is audience and advertisement. Radio PRFM uses social media to reach audiences. And PRFM becomes a medium for the formation of social agents (citizen journalism) and to change the structure of audiences as producers and consumers of citizen news.